2021
DOI: 10.3390/ma14216413
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Influence on Additive Manufactured Carbon Fiber Reinforced Polymer Composites

Abstract: The popular applications of Additive Manufactured (AM) polymer materials in engineering, medical, and industrial fields have been widely recognized due to their high-speed production despite their complex design shapes. Fused Deposition Modeling (FDM) is the technique that has become the most renowned AM process due to its simplicity and because it is the cheapest method. The main objective of this research is to perform a numerical simulation of the thermo-mechanical behaviour of AM polymer with continuous ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…It can be observed from Figure 10 that matrix cracks occurred after the thermally stable treatment, and in the cycled group, the crack was larger. When the specimens were exposed to stable heating (prolonged) for 6 h at 65 C, which is a few degrees above the glass transition temperature of the PLA polymer used, the molecular chains of the polymer changed their structure into an amorphous one, and only local motions of stretching occurred [ 20 ]. In addition to that, the prolonged heating allowed the formation of adsorptive inter-layer bonds and volatile groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed from Figure 10 that matrix cracks occurred after the thermally stable treatment, and in the cycled group, the crack was larger. When the specimens were exposed to stable heating (prolonged) for 6 h at 65 C, which is a few degrees above the glass transition temperature of the PLA polymer used, the molecular chains of the polymer changed their structure into an amorphous one, and only local motions of stretching occurred [ 20 ]. In addition to that, the prolonged heating allowed the formation of adsorptive inter-layer bonds and volatile groups.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that, during a thermal cycling test in an oxidative atmosphere such as air, there was a coupling effect between matrix oxidation, which occurs at the highest temperatures of the cycle, and matrix cracking caused by thermo-mechanical ply stresses caused by prohibited differential expansions of the plies. Previously, heating treatment of unidirectional (UD) continuous CFRP composite at an elevated temperature was experimentally and numerically investigated by Muna et al [ 20 ]. The coupled thermal–displacement analysis was used during the numerical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the Tg of PLA lies between 50 °C and 70 °C [ 42 ]. Based on the Dynamic Mechanical Analysis (DMA), performed on the PLA material, it has the relatively low deflection temperature value as of 42 °C [ 40 ] .…”
Section: Experimental and Numerical Investigationmentioning
confidence: 99%
“…The observed material behaviour is probably related to the deflection temperature of the PLA material. The detailed discussion related to the temperature influence on the PLA material is presented in [ 40 ]. So, the relationship between strain and temperature for temperatures higher than 40 °C was approximated using linear relationship but with different polynomial constants.…”
Section: Experimental and Numerical Investigationmentioning
confidence: 99%
See 1 more Smart Citation